Pendampingan Daily English Conversation untuk Masyarakat Desa Tanjung Belit Kecamatan Kampar Kiri Hulu - Nurdiana Nurdiana; Rizki Fiprinita; Roswati; Afrizal (Anotero Lembaga Scientific Pekanbaru, 2023)
This community service activity aimed to provide a training to members of the Tanjung Belit Tourism Awareness Group (Pokdarwis) about daily English conversations related to the environment, conditions and surrounding culture. This activity was carried out in the following steps: Socialization activity, Community service activities, Assistance in English practice, and Field practice. This activity was attended by the Tanjung Belit communities who are joined in Pokdarwis with a total of 35 members. This assistance ran well because the participants were very enthusiastic to participate in this activity from the beginning to the end of the activities And their English pronunciation have greatly improved than before. Participants can practice daily English conversation and communicate in English confidently.